2009
DOI: 10.1113/expphysiol.2008.045724
|View full text |Cite
|
Sign up to set email alerts
|

Co‐ordination of spontaneous swallowing with respiratory airflow and diaphragmatic and abdominal muscle activity in healthy adult humans

Abstract: Co-ordination of breathing and swallowing is essential for normal pharyngeal function and to protect the airway. To allow for safe passage of a bolus through the pharynx, respiration is interrupted (swallowing apnoea); however, the control of airflow and diaphragmatic activity during swallowing and swallowing apnoea are not fully understood. Here, we validated a new airflow discriminator for detection of respiratory airflow and used it together with diaphragmatic and abdominal electromyography (EMG), spirometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 35 publications
6
50
1
1
Order By: Relevance
“…A study in healthy volunteers showed the occurrence of diaphragmatic activity consistent with active breathholding that preserved the expiratory volume just before swallowing, thereby allowing expiration at the end of the swallowing apnoea [20]. However, this activity was not sufficient to induce breath-holding during swallowing in tracheostomised patients with open tracheostomy tubes, as indicated by the finding in our study and an earlier study [6] of significant and continuous expiratory leakage through the tracheostomy tube during swallowing bracketed by expiration.…”
Section: Discussionsupporting
confidence: 50%
“…A study in healthy volunteers showed the occurrence of diaphragmatic activity consistent with active breathholding that preserved the expiratory volume just before swallowing, thereby allowing expiration at the end of the swallowing apnoea [20]. However, this activity was not sufficient to induce breath-holding during swallowing in tracheostomised patients with open tracheostomy tubes, as indicated by the finding in our study and an earlier study [6] of significant and continuous expiratory leakage through the tracheostomy tube during swallowing bracketed by expiration.…”
Section: Discussionsupporting
confidence: 50%
“…Further analysis should incorporate these important features of aspiration, which can be checked by VFSS. In addition, previous studies have suggested other mechanisms related to airway protection, such as pharyngeal constriction [23], coordination between breathing and swallowing [24], and the sensory regulation of swallowing [25]. In the present study, persistent aspiration after the recovery of swallowing initiation in the nonrecovered group could have resulted from impairments of these mechanisms.…”
Section: Discussionmentioning
confidence: 42%
“…In healthy subjects, experimentally-induced hypercapnia and elastic loading increase respiratory frequency and disrupt the normal breathing-swallowing coordination (11,12). This pattern is similar to what was observed by Terzi et al (5).…”
supporting
confidence: 77%